Prospecting potential evaluation based on geological factor analysis-a case study of Jiaojiacheng ore belt - Ma, Zhaoyang; Qiao, Yakai; Jing, Ming (Frontiers in Earth Science, 2024)
Mineral forecasting is of great significance for social development. As an important aspect of geological exploration, its importance lies not only in its direct contribution to economic growth but also in how it employs precise technical methods for mineral exploration. This study utilizes a geological factor analysis method that combines various complex geological observation factors into a few dominant comprehensive factors, followed by causal research and multivariate statistical analysis for classification. Based on this, the study applies principles and methods of elemental geochemistry to identify the dispersion and concentration patterns of associated elements from the distribution characteristics of ordered accompanying factors, providing a scientific basis for mineralization forecasting. Using geochemical experimental data, geological survey comprehensive profiles, and factor score contour maps, this paper analyzes the southern extension segment of the Jiaojia gold mine mineralization belt through geological factor analysis. It was found that the anomalous distribution of chemical elements F4 (Hg, Au, Pb) exhibits certain regularities, which significantly indicate mineralization information and suggest the presence of two main longitudinal mineralization belts.